Creation of Appsheet-Based Vendor Database System at Savoy Homann Hotel Purchasing Division - Amalina Sawitri; Sri Raharso; Sherry Novalia (Universitas Islam Kuantan Singingi, 2025)
The tourism industry in Indonesia is experiencing rapid development. One of these industries is hospitality as a place for tourists to stay. In carrying out its operations, the hotel depends on vendors to meet the needs of goods and services. Therefore, the vendor selection stage needs to be done properly. An improper selection process can result in a mismatch between the goods received and the needs of the hotel. Based on these problems, this project was created with the aim of building an Appsheet-based vendor database system that contains complete information about vendor data and quality to support a better decision-making process. This project began with a needs analysis through interviews with Savoy Homann Hotel Purchasing. In addition, a literature study was conducted as a reference for designing solutions. Next, the system was developed and tested using the Blackbox Testing method and interviews. As a result, the system successfully fulfills all the company's needs, ranging from vendor data, product quality, to performance ratings. The test shows that the features run well and according to plan. In conclusion, this vendor database system effectively helps the Purchasing division in managing the procurement of goods and services more efficiently, structurally, and optimally.